Associations between oral health and depressive symptoms: Findings from the Concord Health and Ageing in Men Project. (13th January 2020) - Wright, Fredrick A. Clive; Takehara, Sachiko; Stanaway, Fiona F.; Naganathan, Vasi; Blyth, Fiona M.; Hirani, Vasant; Le Couteur, David G.; Handelsman, David J.; Waite, Louise M.; Seibel, Markus J; Cumming, Robert G.
Abstract: Objective: To investigate whether poorer oral health, tooth loss and lower usage of dental services are associated with depressive symptoms in older Australian men. Methods: Cross‐sectional study of data collected from participants of the Concord Health and Ageing in Men Project. Depressive symptoms were evaluated by the Geriatric Depression Scale. Chewing capacity was estimated by ability to chew 11 food items. Results: The prevalence of depressive symptoms was 17.5%. Self‐evaluated oral health, chewing capacity and the number of natural and decayed teeth were associated with depressive symptoms. After adjusting for multiple confounders, chewing capacity (PR 1.93; 95% CI 1.34‐2.79) and decayed teeth (PR 1.68; 95% CI 1.03‐2.75) maintained a significant association with depressive symptoms. Conclusion: The direction of causality between oral health and depression is unclear; however, oral health may contribute to depression in older Australian men and depressive symptoms may limit chewing capacity and be aggravated by untreated dental decay.